Caribbean fish feces are an environmental hotspot of viable Symbiodiniaceae - Titus, K. R.; Castellon, R.; Washington, C.; Cooper, J.; Grupstra, C.; Bloomberg, J.; Coy, S. R.; Farmer, B. H.; Karrick, C. E.; Meiling, S.; Quetel, J.; Rossin, A. M.; et al. (Frontiers in Microbiology, 2026)
Approximately 85% of stony coral species initially acquire their nutritional symbionts (Family Symbiodiniaceae) from the environment (horizontal transmission). Recent studies have identified live Symbiodiniaceae cells in the feces of coral-eating (corallivorous) and herbivore/detritivore fish, and thus these fish could vector Symbiodiniaceae to prospective stony coral hosts. However, nearly all data on viable Symbiodiniaceae cell densities in fish feces are from Pacific reefs. This study quantifies the density and diversity of viable Symbiodiniaceae cells in the feces of six Caribbean corallivore and herbivore/detritivore fish species in the U.S. Virgin Islands, enabling comparisons of consumer-symbiont pathways between ocean basins. Caribbean fish feces contained an average of 5 million viable Symbiodiniaceae cells ml−1, comparable to previously reported values for Pacific corallivores. However, unlike on Pacific reefs, where Symbiodiniaceae cell densities varied in feces by fish trophic group, in the Caribbean, high densities of Symbiodiniaceae cells were documented in fish feces across feeding categories. In Caribbean herbivore/detritivore feces, high Symbiodiniaceae densities likely reflect observed, yet unexpected, feeding by these fishes on corals. Contributions of sloughed diseased coral tissue to detritus on U.S. Virgin Islands reefs may have also increased the number of Symbiodiniaceae cells consumed by detritivorous fishes. Symbiodiniaceae genera Symbiodinium, Breviolum, Cladocopium, Durusdinium, and Fugacium were detected in Caribbean fish feces. These findings demonstrate that corallivore and herbivore/detritivore fish feces constitute environmental hotspots of viable Symbiodiniaceae on Caribbean reefs.